Incentives and Obstacles to the Public Sector and Civil Service Reform: A Conceptual Analysis - van der Meer, Frits M.; Dijkstra, Gerrit (Journal of Public Governance, 2022)
Objectives:In this paper, the nature of incentives and obstacles to public sector and civil service reform is analysed. We will critically examine the popular idea that rationally-conceived reform plans can contribute to reform success. In particular, we will examine the assumption that reform failures can be attributed to a political ‘distortion’ of rationallyconceived reform plans. We will illustrate our analysis with an examination of the (top) civil service reform in the EU27, especially with regard to Eastern European member states.Research Design & Methods:This paper is a conceptual paper. The central question is addressed through a systematic examination of crucial concepts using the civil service reform in the EU27 as an illustration.Findings:The argument that political and bureaucratic obstructions thwart the good intentions of rationally-operating reformers is too one-sided and is not helpful in explaining the reform successes and failures developments in the EU27, and in particular in Eastern European countries. Decisions on these reform issues are highly political, as they involve making binding choices about the future and about the existing problems on behalf of both society and government. This is not a technical and unbiased exercise to be completed by neutral internal or external experts.Implications / Recommendations:Reforms are essentially the product of a long-lasting process of political, administrative, and societal changes. For reforms to be successful, they must match these changes.Contribution / Value Added:Only a corresponding and incremental societal, political, and bureaucratic reform process can offer a solution. Complaints over irrational reform obstacles are thus not only inconducive to successful reforms, but they may actually hinder them.